The theoretical status of the phenomenon of argumentation - Savtchouk, Tatiana N. (Journal of the Belarusian State University. Philology, 2019)
The article is devoted to the explication of the theoretical status of the phenomenon of argumentation. For this purpose, the ways of understanding the concept «argumentation» presented in the scientific literature are being systematized. It is noted that the uncertainty of the semantic and objective meanings of the key concept of argumentology hinders the creation of a reliable theoretical model. The author analyzes three main approaches to the interpretation of the term «argumentation». They focus on different sides of this research object, treating argumentation as a special type of reasoning, as a communicative practice (discourse) or as a cognitive category. Taking into account such interpretations, the author explicates essential features of argumentation and formulates the definition of this notion. The definition characterizes argumentation both as a concept, as a process, and as a product. It is concluded that such a multidimensional understanding of argumentation makes it possible to investigate this phenomenon comprehensively in different types of social and communicative practices and is a precondition for the creation of a convergent theory oriented both at the description and critical analysis of argumentative discourse.